TINJAUAN PELAKSANAAN KEWAJIBAN PT. INSTRUCOM TERHADAP TENAGA KERJA DALAM PERJANJIAN KERJA WAKTU TERTENTU DI KOTA PEKANBARU - Muhammad Tri Wachyu; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
PT. Instrucom one contracting company entered into agreements with a couple of companies. The company is engaged in the oil and gas in the city of Pekanbaru in his efforts can not be separated from cooperation with other companies or other parties that support the smooth and the progress of his business. In the cooperation of PT. Instrucom employs his own workers fatherly obligations in cooperation with other companies, with the cooperation agreement between PT. Instrucom with other companies creating employment agreements and PT. Instrucom that agreement given time. In 2015, workers feel their default done by. Instrucom, breach of contract in question is the late payment of wages of workers. The problems discussed in this thesis is, first, How is the implementation agreement between PT. Instrucom and labor ?, Second, How the settlement of disputes between PT. Instrucom with labor in the event of default?The method of research in this study, using this type of research is sociological / empirical research sites in the PT. Instrucom Pekanbaru, Riau. , In this research, data collection by interview, and literature study. After the data collected then analyzed qualitatively, then conclude with the deductive method is to analyze the problems of the general form into special shapes.From the research results can be concluded, first, in the implementation of the agreement PT. Instrucom and the labor force of Employment Agreement for specific time periods, workers feel aggrieved over the delay in payment of wages by PT. Instrucom, but PT Instrucom not feel the delay in payment of wages to workers because in the unwritten agreement wage payment date tenga tersebu work, so the implementation of the pact have not been going well. Second, the dispute settlement efforts done only by way of summons or warning of the workforce and by way of a bipartite or consultation between workers and the company, but did not produce an agreement. Until now the settlement of a dispute between PT. Instrucom and labor have not found a solution.Keywords: Implementation of Obligations, Specific Time Employment Agreement, PT. Instrucom, Labor